MEASUREMENT OF THERMAL AND LOAD INDUCED CRACK MOVEMENTS IN BITUMINOUS PAVEMENTS - S Lubis, Sutan
Cracks in flexible pavements were investigated to obtain information on their nature and their movements under thermal and traffic stresses. The movement across both transverse and longitudinal cracks was measured by a Demec gauge. For traffic induced measurements a 8,160 kg rear axle load was passed over or close to the cracks at a creep speed. The movement of cracked layers under an overlay may be caused by both thermal and traffic stresses. Temperature changes in a pavement cause the old surface to expand and contract at the crack, creating stresses at the bottom of the overlay. Traffic loads can cause horizontal stresses at the bottom of a new surface as the road deflects under the imposed load. Thermal movements at both longitudinal and transverse cracks were found to be greater than those at uncracked points. The movements were not greatly affected by crack width ; only one of the cracks observed penetrated right through the surface layer, suggesting that cracking had propagated at the surface largely from construction widening operations. Benkelman beam deflection testing using both transient and stop-start procedures was also carried out to measure deflections at selected flexible pavement sections where cracks existed. The maximum deflection and radius of curvature data were related to the movement of each crack position at the corresponding temperature, and good correlations for longitudinal cracks were found to exist.However, crack movements were found to be influenced more by thermal changes than by load. Other factors that influence crack movements, and improved procedures for crack movement measurements have also been discussed. Deflection measurements should be carried out to clarify the effect of cracks on deflection data, but it is suggested that the equipment used to measure crack movement, the Demec gauge, should be improved to minimize human error in measurement. Many analytical procedures with the finite element method, with the purpose of taking into account the presence of cracks, use fracture mechanics principles including crack growth considerations, but the application of crack movement data into overlay design has not yet been satisfactorily fully examined